2020
DOI: 10.1111/ajt.15830
|View full text |Cite
|
Sign up to set email alerts
|

Impact of deceased donor multidrug-resistant bacterial organisms on organ utilization

Abstract: The extent to which donor multidrug‐resistant organisms (MDROs) affect organ utilization remains unclear. We performed a retrospective cohort study at 4 transplant centers between 2015 and 2016 to evaluate this question. All deceased donors who donated at least one organ were included. Exposed donors had at least one MDRO on culture. Unexposed donors had no MDRO‐positive cultures. Only cultures obtained during the donor's terminal hospitalization were evaluated. Multivariable regression was used to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…2,3,5 The lack of association in our study may have again been due to limited power (6% of SOT recipients had a donor with an MDR-Gram negative on culture), but it is not routine practice at the included study sites to treat all MDR-Gram negatives on donor cultures in the recipient, unless identified from the blood or allograft, so our results do raise the question of whether MDR-Gram negatives on donor culture may be less threatening than perceived. 8 Conversely, we did find an association between donor VRE and recipient infection in our unadjusted secondary analyses, suggesting further study of the impact of donor VRE on recipient outcomes is needed. 25 Additionally, future studies evaluating how antimicrobials administered to the recipient affect the association between donor MDROs and recipient infections are needed to better understand these outcomes.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…2,3,5 The lack of association in our study may have again been due to limited power (6% of SOT recipients had a donor with an MDR-Gram negative on culture), but it is not routine practice at the included study sites to treat all MDR-Gram negatives on donor cultures in the recipient, unless identified from the blood or allograft, so our results do raise the question of whether MDR-Gram negatives on donor culture may be less threatening than perceived. 8 Conversely, we did find an association between donor VRE and recipient infection in our unadjusted secondary analyses, suggesting further study of the impact of donor VRE on recipient outcomes is needed. 25 Additionally, future studies evaluating how antimicrobials administered to the recipient affect the association between donor MDROs and recipient infections are needed to better understand these outcomes.…”
Section: Discussionmentioning
confidence: 56%
“…Prior work from our group has shown a notable reduction in organ utilization when MDR-Gram negative organisms are identified on donor culture. 8 Further, MDROs are increasingly being observed among the deceased donor cohort. We have previously reported that approximately 15% of deceased organ donors have at least one MDRO identified on peri-procurement cultures.…”
Section: Introductionmentioning
confidence: 99%
“…The case-fatality rate was regarded as death by any cause within the rst 30 days of the onset of infection [10]. MDR Gram-negative refers to extended-spectrum cephalosporin-resistant Enterobacterales, carbapenem-resistant Enterobacterales (CRE), MDR Pseudomonas aeruginosa, and MDR Acinetobacter baumannii [11].…”
Section: De Nitionmentioning
confidence: 99%
“…[12][13][14] In general, controversy remains over the selection and treatment of organs from infected donors. [15][16][17][18][19] A few guidelines recommend that infected donors receive targeted antimicrobial therapy for at least 24-48 h and recipients should be treated with at least a 7-day course of antibiotic targeted to the organism isolated from the donors. 2,20,21 Nevertheless, treating donors and recipients with prolonged and/ or recurrent antibiotic treatment could promote the emergence of MDR bacteria, cause the uptake and metabolism of suboptimal drugs, including immunosuppressants, and carry the risk of side effects on the other organ systems.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have revealed 3%–10% incidence of CRKP infection in recipients of solid organ transplant with mortality rates ranging from 22% to 72% 12–14 . In general, controversy remains over the selection and treatment of organs from infected donors 15–19 . A few guidelines recommend that infected donors receive targeted antimicrobial therapy for at least 24–48 h and recipients should be treated with at least a 7‐day course of antibiotic targeted to the organism isolated from the donors 2,20,21 .…”
Section: Introductionmentioning
confidence: 99%